Short-Course Raltegravir Intensification Does Not Reduce Persistent Low-Level Viremia in Patients with HIV-1 Suppression during Receipt of Combination Antiretroviral Therapy - McMahon, D.; Jones, J.; Wiegand, A.; Gange, S. J.; Kearney, M.; Palmer, S.; McNulty, S.; Metcalf, J. A.; Acosta, E.; Rehm, C.; Coffin, J. M.; Mellors, J. W.; et al. (Clinical infectious diseases, 2010)
Background. Combination antiretroviral therapy suppresses but does not eradicate human immunodeficiency virus type 1 (HIV-1) in infected persons, and low-level viremia can be detected despite years of suppressive antiretroviral therapy. Short-course (28-day) intensification of standard antiretroviral combination therapy is a useful approach to determine whether complete rounds of HIV-1 replication in rapidly cycling cells contribute to persistent viremia. We investigated whether intensification with the integrase inhibitor raltegravir decreases plasma HIV-1 RNA levels in patients receiving suppressive antiretroviral therapy. Methods. Subjects (n=10) with long-term HIV-1 suppression receiving combination antiretroviral regimens had their regimens intensified for 4 weeks with raltegravir. Plasma HIV-1 RNA level was determined before, during, and after the 4-week intensification period, using a sensitive assay (limit of detection, 0.2 copies of HIV-1 RNA/mL of plasma). A 4-week intensification course was chosen to investigate potential HIV-1 replication in cells with relatively short ( im;1–14-day) half-lives. Results. There was no evidence in any subject of a decline in HIV-1 RNA level during the period of raltegravir intensification or of rebound after discontinuation. Median levels of HIV-1 RNA before (0.17 log10 copies/mL), during (0.04 log10 copies/mL), and after (0.04 log10 copies/mL) raltegravir intensification were not significantly different (Pµ.1 for all comparisons in parametric analyses). High-performance liquid chromatography and mass spectroscopy experiments confirmed that therapeutic levels of raltegravir were achieved in plasma during intensification. Conclusions. Intensification of antiretroviral therapy with a potent HIV-1 integrase inhibitor did not decrease persistent viremia in subjects receiving suppressive regimens, indicating that rapidly cycling cells infected with HIV-1 were not present. Eradication of HIV-1 from infected persons will require new therapeutic approaches. Trial registration. ClinicalTrials.gov identifier: NCT00618371.